Checklist of weeds in University of Port Harcourt and its environs - C Ekeke; C.A. Ogazie; I.O. Agbagwa (Journal of Applied Sciences and Environmental Management, 2019)
We took inventory of the weeds in and around the University of Port Harcourt to determine their family, genus and species compositions and thereby generate their checklist. Three hundred and twenty-two (322) species of weeds belonging to 172 genera and 45 families were identified. Among these weed species, the grasses (Poaceae) having 72 species and 40 genera was the dominant weed identified. This is followed by Fabaceae (25 species in 16 genera), Cyperaceae (53 species in 14 genera), Asteraceae (15 species in 12 genera) and Commelinaceae (20 species in 8 genera). Others include Tiliaceae (7 species in 6 genera), Euphorbiaceae (13 species in 7 genera), Amaranthaceae (5 species in 4 genera), Rubiaceae (6 species in 5), Convolvulaceae (10 species in 4 genera), Solanaceae (8 species in 4 genera), Cucurbitaceae (5 species in 4 genera), Malvaceae (7 species 3 genera) and Verbenaceae (5 species in 3 genera). Anacardiaceae, Asclepiadaceae, Boraginaceae, Crassulaceae, Hydrophyllaceae, Loganiceae, Lythraceae, Melastomataceae, Sapinaceae, Sapindaceae, Selaginellaceae, Sphenocleaceae, Sterculiaceae and Urticaceae with one species in one genus were the least dominant families. These weeds are found in wet or dry land (open fields, cultivated Lands, abandoned fallow and lawns) but predominantly found in open fields. The Perennials (54.98%) are the dominant weeds followed by annuals (42.42%) while bi-annuals (2.60%) were the least. The broad leaves were the dominant weeds and constituted 76.47% of the weeds identified, followed by grasses 14.03% and sedges 9.50%. This finding, therefore, presents the first comprehensive inventory of weeds in the University of Port Harcourt.